ANALISIS BENTUK –TA DAN –TEIRU SEBGAI PENANDA ASPEK DALAM BAHASA JEPANG SERTA PADANNYA DALAM BAHASA INDONESIA - Rizcha Retna Diah; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study discusses about analysis of -ta and -teiru as a marker of aspects of Japanese and equivalents in Indonesian. The purpose of this study is to find out what different of Ta and -teiru and the corresponding equivalent in Indonesian. The data of this study are sentences in the form of –ta and –teiru from Kimi no Nawa and Nihongo Bunkei Ziten. This study uses the translational equivalent method and the determining element sorting technique. The results of this study indicate that the types of verbs found in the form sentences –ta and –teiru are stative verbs, movement verbs, and continuative verbs and verb types affect the type of aspect. The meaning of the aspects carried by the form -ta and -teiru is durative, intensive, accumulative, commututive, and progressive. Match corresponding to each sentence can be interpreted with a moderate, middle, again, has been, is and has been, or could be interpreted as meaning of the verb itself. However, not all forms of Ta and -teiru can be paired with a moderate, middle, again, it's been, are, or have been for the type of verbs also affect whether the verb can be paired with a moderate, middle or longer. Affixation ter- and ber- on hirogatteiru verb 'lie' and hikatteiru 'glowing' also affects the type of verb.Key Words: Aspects, verbs, equivalents